DEVELOPMENT OF MACAMI (MARI MEMBACA DAN MEMAHAMI) INSTRUMENT USING MACROMEDIA FLASH 8 IN PRIMARY SCHOOLS - Dewi, Ermaida (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The background of this research is an instrument of learning for reading comprehension which in general is still dominated by an instrument in the form of print out which makes the students’ interest to read is reduced. In addition, this instrument is usually done manually or handwritten so that the students’ work must be corrected manually and require some time to get the results. This study aims to develop instruments or measuring devices for reading comprehension in the Primary School in Pekanbaru and find out the feasibility of measuring devices for reading comprehension skills. This product is Macromedia Flash 8 based namely "MaCaMi" which stands for Mari Membaca dan Memahami. The research method used was the 4D model with four stages, such as the define stage, the design phase, the develop phase, and the dessiminate stage which is limited to the third stage. The data of this study were obtained from product design expert validation questionnaire, questionnaire validated by linguists, teacher response questionnaire and students response questionnaire. The data were generated quantitatively and analyzed by using the assessment criteria to determine the product quality. The results of this study showed the assessment of product design experts in draft 1 had an average percentage of 69.61% with the appropriate category then had increased in draft 2 to 90.56% with the very feasible category. The results of the feasibility test by linguists in draft 1 had average percentage of 95.30% with the very feasible category then increased in draft 2 to 97.20% with the very feasible category. The results of the teacher's response to the reading comprehension measuring instrument in the Primary School in Pekanbaru developed by researchers obtained an average percentage of 93.50% with a very good category and the results of students' responses to the measuring instrument obtained an average percentage of 89.90% with a category very good. Based on these results, it can be concluded that the product developed by researchers is feasible to be used as a measure of reading comprehension ability of primary school students.